Preventing lesions of nasal septum in preterm newborns: an integrative literature review - Suely de Fátima Santos Freire Bonfim; Simone Maria Muniz da Silva Bezerra; Maria Gorete Lucena de Vasconcelos; Luciana Pedrosa Leal (Universidade Federal de Goias, 2014)
The goal of this study is to investigate scientific evidence related to nursing care for preventing lesions of the nasal septum in preterm infants who are using nasal prong ventilation.  It is an integrative literature review through LILACS, BDENF, CINAHAL, PUBMED and SciELO library electronic databases. We selected 09 studies between 2000 and 2013, available online or through the author, published in Portuguese, English and Spanish. The results displayed that 70% of the studies examine the quality and adaptation of nasal devices and the nursing team's continual vigilance. Septum and nasal columella inspection, hydrocolloid protection and adequate system installation were considered important factors which contribute towards preventing lesions. We conclude that the adaptation of nursing care and constant monitoring of the device and of the newborn during ventilation are necessary to prevent nasal septum lesions. doi: 10.5216/ree.v16i2.21350.